2013
DOI: 10.1200/jco.2011.40.6272
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Rituximab to Chlorambucil Produces Superior Event-Free Survival in the Treatment of Patients With Extranodal Marginal-Zone B-Cell Lymphoma: 5-Year Analysis of the IELSG-19 Randomized Study

Abstract: Both treatments were active; the better response rate and EFS obtained with the addition of rituximab did not translate into improved OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
138
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 25 publications
0
138
0
2
Order By: Relevance
“…6 Zucca et al have recently reported a randomised study comparing chlorambucil versus chlorambucil plus rituximab and concluded that although both treatments were active, a higher complete remission rate and 5-year event-free survival were achieved with combined therapy. 16 With regard to clinical and endoscopic presentation, in our series most patients presented with dyspeptic symptoms (only 11% showed B symptoms) and the more frequent endoscopic findings were erosions and ulcers most often localised in the antrum. This is in accordance with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…6 Zucca et al have recently reported a randomised study comparing chlorambucil versus chlorambucil plus rituximab and concluded that although both treatments were active, a higher complete remission rate and 5-year event-free survival were achieved with combined therapy. 16 With regard to clinical and endoscopic presentation, in our series most patients presented with dyspeptic symptoms (only 11% showed B symptoms) and the more frequent endoscopic findings were erosions and ulcers most often localised in the antrum. This is in accordance with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab in combination with chemotherapy (alkylating agents or purine analogs) has shown ORRs of 85% to 93% (CR in 54% to 78%) in predominantly chemotherapynaive or treatment-naive patients. 4,5,9,12,26 In the relapsed setting, a retrospective analysis of 26 patients with extranodal MZL (no prior systemic antitumor therapy in 10 patients; 38%) treated with rituximab combined with cyclophosphamide, doxorubicin/mitoxantrone, vincristine, and prednisolone (R-CHOP or R-CNOP) showed an ORR of 77% (CR in 23%) with 85% of patients in continuous remission after a median follow-up of 19 months.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Treatment of MZL ranges from localized to palliative approaches; however, for advanced disease, treatments range from single-agent chemotherapy or anti-CD20 monoclonal antibody to a more aggressive approach with chemoimmunotherapy. [4][5][6][7][8][9][10][11][12] Advanced disease is generally incurable, and the majority of patients will experience serial relapses. At the time of study initiation, no therapeutic agent was US Food and Drug Administration (FDA)-approved specifically for MZL, and no standard treatment existed.…”
Section: Introductionmentioning
confidence: 99%
“…This trial compared chlorambucil alone to rituximab alone and to the combination of rituximab and chlorambucil (R-chlorambucil) as front-line therapy in MALT lymphoma patients, with event-free survival (EFS) as the primary endpoint. 23,24 Patients were stratified according to tumor site (gastric vs nongastric), nodal involvement, prior local therapy, and IPI risk group.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…We therefore sought to develop a MALT lymphoma IPI (MALT-IPI) for patients treated during the rituximab era by developing a model using the patient data set of the largest recent controlled clinical trial in MALT lymphoma, namely the International Extranodal Lymphoma Study Group 19 (IELSG-19) randomized study, conducted by the International Extranodal Lymphoma Study Group in 6 European countries, which showed the superiority of the combination of chlorambucil and rituximab in comparison with either rituximab or chlorambucil given as single agents. 23,24 Patients and methods…”
Section: Introductionmentioning
confidence: 99%